2019
DOI: 10.14710/ijred.8.2.119-132
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of the metal parts of diesel engines in biodiesel-based fuels

Abstract: Biodiesel, an environmentally-friendly bio-fuel, has been regarded as one of the most promising alternatives to fossil fuels whose use is rampant in the transportation sector. However, it is important that the corrosive effects of this fuel on engines are studied. This work reviews the corrosiveness that biodiesel exerts on various engine components, especially those made out of metals. First, an analysis of the corrosion mechanisms of metals exposed to biodiesel is provided. The conventional and advanced anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 83 publications
0
17
0
1
Order By: Relevance
“…Bioethanol produced from different types of biomasses is becoming nowadays one of the promising renewable biofuels, unlike non-renewable petroleum-based fuels. Bioethanol blended fuel is generally used as a gasoline additive in ordinary vehicles in most parts of the world, where the fuel system and engine parts are mostly composed by the metallic substances like iron, copper and aluminum, and their alloys so on [6]. The global bioethanol industry has witnessed high growth primarily because of the mandatory usage of bioethanol fuel blends, especially in transportation vehicles in many countries those are looking for an alternative fuel source with less greenhouse gases (GHG) emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Bioethanol produced from different types of biomasses is becoming nowadays one of the promising renewable biofuels, unlike non-renewable petroleum-based fuels. Bioethanol blended fuel is generally used as a gasoline additive in ordinary vehicles in most parts of the world, where the fuel system and engine parts are mostly composed by the metallic substances like iron, copper and aluminum, and their alloys so on [6]. The global bioethanol industry has witnessed high growth primarily because of the mandatory usage of bioethanol fuel blends, especially in transportation vehicles in many countries those are looking for an alternative fuel source with less greenhouse gases (GHG) emissions.…”
Section: Introductionmentioning
confidence: 99%
“…A high S content can affect the performance of engines [91], and the maximum limit set for sulphur in biodiesel is 10 mg/L [70,92]. It was observed that both biodiesels passed this test, which reduces corrosion in fuel containers [12]. The main source of metals in vegetable oil is either its presence in raw material or contact with the manufacturing process and storage [40], as degradation and contamination happen due to undesirable compounds in the engine [31].…”
Section: Elemental Content Analysis 241 Icp-oes Analysis In Virgin Waste Sunflower and Palm Oil And Their Biodieselsmentioning
confidence: 99%
“…The presence of inorganic constituents in biodiesel can affect the quality of the fuel and cause the malfunctioning of engines [87], and since different materials are used for storage containers and engine parts, there is an issue with compatibility [93]. Corrosion in biodiesel is mainly due to the component nature and composition of biodiesel, as well as the environment [12,94]. Metallic storage tanks such as stainless steel and Al are normally used for storage [95], while in automobiles, the fuel is in direct contact with various parts of the engine like the fuel pump, fuel injector, pistons and piston rings, which are made of Cu, Al, brass-Br (copper-rich alloy) and bronze [93].…”
Section: Elemental Content Analysis 241 Icp-oes Analysis In Virgin Waste Sunflower and Palm Oil And Their Biodieselsmentioning
confidence: 99%
See 2 more Smart Citations